Surgery in Jehovah’s Witnesses – our experience - Trzciński, Radzisław; Kujawski, Ryszard; Mik, Michał; Berut, Maciej; Dziki, Łukasz; Dziki, Adam (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Surgeons face a special challenge in treating Jehovah’s Witnesses who refuse blood transfusion. Aim: To present our surgical experience with this group of patients operated on in our department. Material and methods : A retrospective study of 16 unselected Jehovah’s Witnesses patients was conducted between October 2004 and February 2012. We analysed gender, age, haemogram before and after surgery, types of surgery, postoperative complications and the need for blood transfusion, and/or other drugs stimulating erythrogenesis. Results: Eighty-one percent of patients were women; the average age of all patients was 57.3 years. Mean haemoglobin level, preoperative, postoperative, and on the day of discharge from hospital, was 12.5 g/dl, 9.7 g/dl, and 9.29 g/dl, respectively. Over the same time period, mean red blood cell count was 4.53 mln/µl, 3.58 mln/µl, and 3.37 mln/µl, respectively. Two out of 16 patients agreed to have blood transfusion. Drugs used for erythropoiesis stimulation included rEPO, ferrum, and folic acid. No surgical death was noted. Conclusions : We found that abdominal surgery was safe in our small group of Jehovah’s Witness patients. However, all Jehovah’s Witness patients should be fully informed about the type of procedure and possible consequences of blood transfusion refusal. Two of our patients agreed to blood transfusion in the face of risk of death.